TECHNICAL TRAINING: A PATHWAY TO YOUTH EMPOWERMENT - Ohagwu, Onyekachi Marcellinus (MATTER: International Journal of Science and Technology, 2020)
This paper assessed the relevance of technical training as an empowerment tool for youth in Sarawak – hence it shed light on Technical and Vocational Education Training (TVET) as a pathway to youth empowerment. It is noted that TVET increases youth empowerment opportunities and social-economic development. Qualitative research methodological approach was adopted in this study and the findings show that TVET is a tool for positive change with various potentials for skill development, capacity building, wealth creation, and youth empowerment.